Experimental Study on Soil Hardening Model Parameters of First-stage Terrace of Yangtze River in Wuhan - LI Guang-cheng, SHAO Yong, Yi Pan-pan, WANG Lu, CHEN Ming, MA Lu-han (长江科学院院报)
A series of physical property tests, consolidation tests, and unloading-reloading tests were conducted on undisturbed soil samples of silty clay, silt, and fine sand from the first-stage terrace of Yangtze River in Wuhan. The indoor experimental values of modified Mohr-Coulomb model parameters, including E o e d r e f, E 50 r e f, E u r r e f,c',φ',and Rf for typical soil layers with upper clay layer and lower sand layer in this terrace, were directly acquired. Using experimental data, adjusted experimental data, and empirical data from other regions in China, the relationships among different modulus parameters of typical soil layers in this region were analyzed. Moreover, the effective strength indexes were compared with the current provincial standard specification. The parameters obtained from this experimental study can be comprehensively selected and applied in areas with similar engineering geological background conditions. Additionally, they can offer valuable references for geotechnical engineering finite element parameter inversion analysis, parameter sensitivity analysis, and parameter applicability correction, which are based on the finite - element modeling experience of actual foundation pit engineering and the monitoring data of foundation pit engineering examples.